Head Ultrasound Findings in Infants with Birth Weight >1,500 g and Gestational Age >32 Weeks Exposed to Prenatal Opioids - Sakaria, Rishika P.; Rana, Divya; Harsono, Mimily; Cohen, Harris L.; Pourcyrous, Massroor (American Journal of Perinatology, 2025)
This study aimed to evaluate the effects of prenatal exposure to opioids on head ultrasound (HUS) and to determine the need for routine HUS evaluation in infants exposed to prenatal opioids.This is a retrospective cohort study performed at a level III NICU. Infants >32 weeks gestational age and >1,500 g birth weight with prenatal opioid exposure (n = 127) were included in this study. Data including demographic information and HUS results were recorded.Twenty (16%) infants were exposed to opioids only whereas the rest of the infants (84%) were exposed to opioids plus other drugs (polysubstance) in utero. Sixteen of 127 infants (13%) had abnormal initial HUS. Sub-ependymal hemorrhage or grade 1 intraventricular hemorrhage was the most common abnormal finding. Absent septum pellucidum was seen in three infants.A relatively large proportion (13%) of infants in this study had abnormal HUS findings; however, further studies are required to correlate HUS findings with a specific drug of exposure, duration of exposure, polysubstance use, umbilical cord drug concentration levels, and neurodevelopmental outcomes.
Keywords: intraventricular hemorrhage; head ultrasounds; late preterm; term neonates; maternal opioid use